2000
DOI: 10.1038/sj.bmt.1702127
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a BMT support group

Abstract: References1 Takeda S, Ito K, Sakura T et al. Three AML patients with existing or pre-existing intracerebral granulocytic sarcomas who were successfully treated with allogeneic bone marrow transplantation. Bone Marrow Transplant 1999; 23: 731-734. 2 Oehmichen M, Domasch D, Wietholter H. Origin, proliferation, and fate of cerebrospinal fluid cells. A review on cerebrospinal fluid cell kinetics. J Neurol 1982; 227: 145-150. 3 Coriat AM, Muller U, Harry JL et al. PCR amplification of SRY-related gene sequences rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Is a mixture of ages included? For example, some institutions do not permit pediatric and young chil-Sherman, Cooke, and Grant 17 dren to be in the same group as adults (Marks and Benjamin, 2000). Are caregivers included, not included, and/or is there a separate group for caregivers?…”
Section: Implications For Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Is a mixture of ages included? For example, some institutions do not permit pediatric and young chil-Sherman, Cooke, and Grant 17 dren to be in the same group as adults (Marks and Benjamin, 2000). Are caregivers included, not included, and/or is there a separate group for caregivers?…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…In establishing a support group for a group of BMT patients, Marks and Benjamin (2000) reported that their group wanted to meet somewhere other than the hospital. This may not always be feasible if funding for such a resource is not available.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For patients with solid tumours or chronic diseases, support groups have emerged over the past three decades as a successful tool for coping with the evolving stress associated with the disease and/or diagnostic or therapeutic procedures [ 25 28 ]. However, scientific data on support groups for HCT survivors are scarce [ 10 , 11 , 29 – 32 ]. With this prospective study, we report on establishing a support group for patients after allogeneic HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific data on support groups for these patients are scarce. More than 20 years ago, Marks and Benjamin reported on the establishment of a support group for patients after allogeneic HCT [ 10 ]. Lounsberry et al published a feasibility study of a telehealth-delivered psychoeducational support group for patients after allogeneic HCT in 2010 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%